Days of destiny : crossroads in American history : America's greatest historians examine thirty-one uncelebrated days that changed the course of history - McPherson, James M.; Brinkley, Alan. (New York : DK Pub., 2001)
Contains thirty-one essays in which the authors, all historians, discuss specific, under-recognized events they believe helped shape America and the world.
Introduction / James M. McPherson and Alan Brinkley -- June 17, 1675 : King Philip's quarell / James Axtell -- October 23, 1740 : Whitefield awakens America / John Demos -- May 24, 1775 : Silas Deane's diary / Jack N. Rakove -- October 19, 1781 : the Battle of Yorktown / Robert Middlekauff -- July 16, 1787 : the day the constitution was saved / Gordon S. Wood -- June 20, 1790 : Mr. Jefferson's dinner party / Joseph J. Ellis -- March 4, 1801 : the second American Revolution / Joyce Appleby -- Mid-February 1824 : the way West / William H. Goetzmann -- January 1, 1831 : the liberator / Ira Berlin -- July 20, 1848 : the Seneca Falls Convention / Christine Stansell -- March 6, 1857 : the day of Dred Scott / Sean Wilentz -- September 13, 1862 : the lost orders / James M. McPherson -- June 13, 1866 : equality before the law / Eric Foner -- October 5, 1877 : "I will fight no more forever" / Elliott West -- February 24, 1908 : affirming the sexual divison of labor / Alice Kessler-Harris -- August 14, 1908 : the end of accommodation / David Levering Lewis -- January 1, 1913 : the routine arrest that launched a revolution / Geoffrey C. Ward -- June 20, 1917 : the great demand / Nancy F. Cott -- July 20, 1925 : the Scopes trial : Darrow v. Bryan / Alan Brinkley -- May 22, 1933 : Harry Hopkins brings relief / Linda Gordon -- April 2, 1943 : testing America / Nicholas Lemann -- July 25, 1945 : "the most terrible bomb in the history of the world" / John W. Dower -- September 19, 1946 : the president learns about civil rights / William E. Leuchtenburg -- May 3, 1948 : Hollywood at the crossroads / Ann Douglas -- January 17, 1961 : a farewell to arms / Douglas Brinkley -- June 21, 1961 : the decision to publish Kuhn / David A. Hollinger -- July 28, 1965 : end of an era, start of a war / David Kaiser -- January 14, 1967 : the human be-in / David Farber -- July 12, 1967 : days of rage : the life and death of Newark / Kenneth T. Jackson -- November 22, 1971 : Sally Reed demands equal treatment / Linda K. Kerber -- June 14, 1973 : the battle over biotechnology / Daniel J. Kevles.
Includes index.
79471
Keywords: Anecdotes -- United States